1994
DOI: 10.1007/bf00004807
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns in the fish assemblages of individual pools in a midwestern stream (U.S.A.)

Abstract: The composition and consistency of fish assemblages in 14 adjacent pools (6-120 m long) of a clear-water, limestone and gravel creek in midwestern U.S.A. were quantified in eight snorkeling surveys over 19 months, to establish a baseline of natural variation in the system at this scale. The fauna of the stream was dominated numerically by minnows (Cyprinidae), sunfish and black bass (Centrarchidae), and topminnows (Fundulidae). The pool fish fauna of the total 1 km reach (including all 14 pools) was highly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 41 publications
7
86
0
Order By: Relevance
“…The greatest richness and density occurred during the summer and fall periods, with a total of 23 species and average unit densities ranging from 4.9 to 218.6 fish per 100 m 2 . Others found the same seasonal patterns of use where feeding, resting, evasion from predation, and spawning were the dominant trait strategies [172,178,179,193,194,197,198,201,203,[214][215][216]. Schwartz and Herricks (2008) [79] found that feeding strategy could be summarized as: insectivores mainly occupying the pool-front unit, omnivores in the scour pool unit, piscivores in the pool-mid unit, and herbivores in the glide and riffle with raceway unit.…”
Section: Submerged Barmentioning
confidence: 96%
See 1 more Smart Citation
“…The greatest richness and density occurred during the summer and fall periods, with a total of 23 species and average unit densities ranging from 4.9 to 218.6 fish per 100 m 2 . Others found the same seasonal patterns of use where feeding, resting, evasion from predation, and spawning were the dominant trait strategies [172,178,179,193,194,197,198,201,203,[214][215][216]. Schwartz and Herricks (2008) [79] found that feeding strategy could be summarized as: insectivores mainly occupying the pool-front unit, omnivores in the scour pool unit, piscivores in the pool-mid unit, and herbivores in the glide and riffle with raceway unit.…”
Section: Submerged Barmentioning
confidence: 96%
“…Within the mesohabitat scale, differential habitat use by fish between pools and riffles has been extensively studied [77,123,175,[193][194][195][196][197][198][199]. It was observed from these studies that pools and riffles locally diversify lotic conditions providing strong abiotic environmental controls on fish distribution and abundance.…”
Section: Applied Ecological Concepts At the Mesohabitat Scalementioning
confidence: 99%
“…1). Phylogenetic affiliations have been documented from scales ranging from assemblages of meso-habitats (MATTHEWS et al, 1994) in local communities to régional ichthyofaunas (ROBERTS, 1975 ;LEVEQUE et al, 1990, LUNDBERG, 1993. At the local scale, contemporary ecological factors, rather than historical factors, are of primary interest, although barriers to local dispersai have played a key rôle in some cases (ENDLER, 1982).…”
Section: Phylogenetic Diversitymentioning
confidence: 99%
“…Fish populations inhabiting lowland river Systems are periodically subdivided into local subunits within floodplain lagoons and later reunited with conspecifics from other subunits during annual floods (JUNK et al, 1989 ; WELCOMME, 1979). Most stream fish populations are subdivided into habitat subunits with variable amounts of migration between them (ELLIOT, 1987 ; FRASER & CERRI, 1982 ;MATTHEWS et al, 1994 ;SCHLOSSER, 1982). PULLIAM's (1988) BIDE model may be particularly appropriate for stream fish populations subdivided by mesohabitats.…”
Section: Population Diversitymentioning
confidence: 99%
See 1 more Smart Citation